Effect of different level of energy and crude fiber from sawdust in diets on carcass quality of broiler - Mandey, J. S.; Kowel, Y. H. S.; Regar, M. N.; Leke, J. R. (Diponegoro University, 2017)
This study was conducted to investigate the effect of different level of energy and crude fiber in diets containing sawdust on carcass quality of broilers. A total of 120 broilers were used for the research. The experiment utilized a completely randomized design in 2 x 3 factorial arrangement of treatments consisting of two dietary concentrations of energy and three dietary concentrations of crude fiber. Each treatment consisted of 4 replications (5 birds each) was reared during 35 days. The birds were housed in battery cages with ad libitum access to feed and water. During the experiment, feed intake, carcass yield, abdominal fat, blood LDL-cholesterol and HDL-cholesterol were measured. Data were subjected to the analysis of variance test followed by least significant difference test (LSD). Results showed that the diet with 3,100 Kcal/kg ME and 11% crude fiber significantly decreased feed intake, abdominal fat percentage, and blood LDL-cholesterol, but did not affect final body weight and the value of blood HDL-cholesterol and had the good value of carcass percentage. The diets containing sawdust with higher level of energy content decreased feed intake and the higher level of crude fiber decreased final body weight, carcass percentage and abdominal fat. Optimum broiler performance and carcass quality was obtained by diet formulated to contain 3100 Kcal/kg ME and 11% crude fiber.